Dietary L-tryptophan alters aggression in juvenile matrinxa Brycon amazonicus - Bejo Wolkers, Carla Patricia [UNESP]; Serra, Monica [UNESP]; Hoshiba, Marcio Aquio [UNESP]; Urbinati, Elisabeth Criscuolo [UNESP] (Springer, 2012)
This study evaluated the effect of dietary supplementation with -tryptophan (L-TRP), a serotonin precursor, on the aggressiveness of juvenile matrinx . Fish were kept in individual aquaria for 7 days receiving the diets: D1 (control: 0.47% of TRP), D2 (0.94% of TRP), D3 (1.88% of TRP), and D4 (3.76% of TRP). After this, they were grouped with an intruder fish to establish a resident-intruder relationship during periods of 20 min. Blood cortisol, glucose, chloride, sodium and calcium; hemoglobin, hematocrit, red blood cell count and volume; liver glycogen and lipids were measured. Territoriality had significant effect on the aggressiveness of matrinx (the residents were more aggressive than intruders, < 0.001) and tryptophan significantly affected their behavior. Fish fed with the D2 diet presented a longer latency until the first attack ( = 0.0069) and bit the intruder fewer times ( = 0.0136) during the period of observation, compared to the control group. The frequency of bites and chases after the first attack was not affected by the dietary supplementation of TRP. Physiological variables were not significantly affected by the diet, except for a moderate increase in cortisol level in fish fed with D2 diet after the fight, indicating slight activation of the hypothalamus-pituitary-interrenal axis. The results show that juvenile matrinx have aggressive and territorial behavior and that a diet containing 9.4 g TRP kg(-1) alter their aggressiveness, without affecting the stress-related physiological parameters.
Keywords: Brycon amazonicus; Matrinxa; Aggressiveness; Social stress; Tryptophan